1996
DOI: 10.1002/j.1460-2075.1996.tb01016.x
|View full text |Cite
|
Sign up to set email alerts
|

The rapid inactivation of nuclear tyrosine phosphorylated Stat1 depends upon a protein tyrosine phosphatase.

Abstract: After interferon‐gamma (IFN‐gamma) treatment of cells the appearance of tyrosine phosphorylated Stat1 in the nucleus was maximal within 20–30 min, remained for 2–2.5 h and activated molecules disappeared by 4 h. In the absence of continued signaling from the receptor (imposed by staurosporine treatment) previously activated Stat1 disappeared completely within 60 min, implying continuous generation and removal of active molecules during extended IFN‐gamma treatment. Proteasome inhibitors prolonged the time of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
217
3
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(241 citation statements)
references
References 38 publications
18
217
3
2
Order By: Relevance
“…We considered, then, the possibility that the ␣-GFP-siRNA expression could induce the interferon (IFN) system. One standard test to check for IFN system activation is to measure the level of the STAT1 protein, known to be upregulated in response to IFN (22). In regular A549 cells and A549-LV-NGFR control cells, as well as in A549-LV-siGFP cells, mock IFN treated and mock infected, STAT1 levels remained at the background level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We considered, then, the possibility that the ␣-GFP-siRNA expression could induce the interferon (IFN) system. One standard test to check for IFN system activation is to measure the level of the STAT1 protein, known to be upregulated in response to IFN (22). In regular A549 cells and A549-LV-NGFR control cells, as well as in A549-LV-siGFP cells, mock IFN treated and mock infected, STAT1 levels remained at the background level (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The latter result has several implications: (1) at least a portion of the induced STAT1 was phosphorylated, since phosphorylation is necessary for STAT1 DNA binding; (2) some active or phosphorylated STAT2 must also be present, since the ISGF3 complex requires active STAT1 and STAT2 as well as the ISGF3g (p48) member of the IRF family. However, STAT1 and STAT2 phosphorylation and DNA binding normally only occurs upon IFN-a/b induction Haspel et al, 1996;Shuai et al, 1993). It would be of relevance to see whether the induced STAT1 is su cient to initiate activation of itself, as well as STAT2.…”
Section: Discussionmentioning
confidence: 99%
“…Also interesting was the observation that although IFN stimulation of Dox-induced rtTA-IRF-1 and rtTA-IRF/RelA cells resulted in enhanced ISGF3 binding, DNA binding activity was not relatively higher than levels obtained in IFN-stimulated control cells, despite higher STAT1 protein levels. This phenomenon may be due to the constitutive activation/inactivation cycle of the STAT proteins Haspel et al, 1996), such that only a certain percentage of STAT protein is activated and binds DNA at any given time.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that STAT signals can be inactivated by dephosphorylation of the conserved tyrosine through tyrosine phosphatase(s) (Haspel and Darnell, 1999;Haspel et al, 1996;Shuai et al, 1996). This can also be achieved by ubiquitin/proteasome-mediated degradation of the STAT proteins (Kim and Maniatis, 1996;Yu and Burako , 1997), or by a direct inhibition through a more classical negative feedback loop mediated by CIS/SOCS/JAB/SSI family of proteins (Kovanen and Leonard, 1999).…”
Section: How Are Il-2-activated Stat5 Signals Turned O ?mentioning
confidence: 99%